Drug resistance testing in hepatitis C therapy. (March 2012) - Poveda, Eva; Soriano, Vincent
The first direct-acting antivirals (DAAs) have recently been approved for the treatment of chronic HCV infection. These molecules interact with different HCV proteins, including NS3/4A protease, NS5B polymerase and NS5A. Several compounds belonging to distinct drug families are in the advanced stages of clinical development. Whereas most DAAs have demonstrated a potent antiviral activity against HCV, emergence of drug resistance represents a huge challenge with almost all of these drugs. The use of combination therapy greatly increases the chances of achieving rapid and complete viral suppression, preventing selection of DAA resistance. Drug resistance mutations and pathways differ according to antiviral agents and HCV genotypes/subtypes. HCV subtype 1a displays a uniformly lower barrier to resistance than HCV subtype 1b when confronting most HCV protease inhibitors, NS5B non-nucleoside inhibitors and NS5A inhibitors. Broad cross-resistance exists between drugs belonging to the same family, except for NS5B non-nucleoside analogs that may exhibit at least four distinct drug resistance profiles. Second-generation inhibitors are in development that may overcome the reduced susceptibility caused by single mutations. The large genetic variability of HCV suggests that some drug resistance changes may exist as natural polymorphisms in certain HCV geno/subtypes at rates that may require the consideration drug resistance testing before recommending certain antivirals.